Success rate of short unitary implants installed in atrophic mandible: Integrative Review - do Vale Souza, J. P. [UNESP] (2022)
Introduction: In the rehabilitation of total edentulous patients, lack of bone availability in posterior maxillary regions is common due to pneumatization of the maxillary sinus and posterior mandible due to the presence of the lower alveolar nerve. And to rehabilitate this type of patient, one of them is the use of short implants. Methods: The work aims to evaluate the success rate of treatment of short implants through a literature review. The search was carried out in august 2020 in the Pubmed (MedLine), Scopus and Embase databases, using the keywords: extra short implants, short implants, survival rate, single implant, atrophic mandible. The keywords followed the AND or OR criteria previously elaborated by the PICO question. The inclu-sion criteria were: implants with a length of 4 to 8 mm, which were single and in the posterior region of atrophic mandible and which had 5 years of follow-up. Articles were excluded from the review where the implants were splinted, had a follow-up of less than 5 years and considered short implants larger than 8 mm. Results: After the search, 4 articles were separated, which totaled an n = 172 short implants obtaining a success rate of 93.47% in 5 years. After the search, 4 articles were separated, which totaled an n = 172 short implants obtaining a success rate of 93.47% in 5 years. Conclusion: We can conclude that the use of short implants, even in single prostheses, has a high success rate, which can provide the edentulous patient with little bone bioavailability for rehabilitation.